The Duration of Marginal Employment in West Germany: A Survival Analysis Based on Spell Data - Jürgen Kolb; Axel Werwatz (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
We use data from the German Socio-Economic Panel from 1984 to 1995 to analyze longitudinal aspects of marginal employment (geringfügige Beschäftigung) in West Germany. After discussing problems of identifying marginal employment spells, we document that marginal employment spell vary considerably in the German labor market. Spell duration in our data ranges from one month to 12 years or more. Marginal employment, however, is typically limited to brief episodes. Our results suggest that the duration of marginal employment spells is influenced by institutional factors that favor the employment of housewives. In general, marginal employment seems to be a flexible option to adapt labor supply behavior to various phases of the life cycle.
Keywords: 330; Atypische Beschäftigung; Dauer; Weibliche Arbeitskräfte; Erwerbsverlauf; Deutschland